2020
DOI: 10.1111/jam.14786
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt concentration on microbial communities, physicochemical properties and metabolite profile during spontaneous fermentation of Chinese northeast sauerkraut

Abstract: Aim The aim of this study was to study the effects of salt concentrations on the microbial communities, physicochemical properties, metabolome profiles and sensory characteristics during the fermentation of traditional northeast sauerkraut. Methods and Results Northeast sauerkraut was spontaneously fermented under four salt concentrations (0·5, 1·5, 2·5 and 3·5%, w/w). The result of microbiological analysis showed that the population of lactic acid bacteria in 2·5%‐salted sauerkraut was significantly higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
2
16
0
2
Order By: Relevance
“…To further investigate the effect of salt concentration on fermented vegetables, we performed a non-targeted metabolite analysis using mass spectrometry along with multivariate statistical analysis ( Lee et al., 2021 ; Seo et al., 2018 ; Yang et al., 2020 ). Although several studies have reported the effect of salt type on kimchi fermentation ( Chang et al., 2011 ; Kim and Kim, 2014 ), few studies have reported the correlation between salt type and corresponding metabolites and microbial community ( Kim et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…To further investigate the effect of salt concentration on fermented vegetables, we performed a non-targeted metabolite analysis using mass spectrometry along with multivariate statistical analysis ( Lee et al., 2021 ; Seo et al., 2018 ; Yang et al., 2020 ). Although several studies have reported the effect of salt type on kimchi fermentation ( Chang et al., 2011 ; Kim and Kim, 2014 ), few studies have reported the correlation between salt type and corresponding metabolites and microbial community ( Kim et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, tolerance to NaCl may offer a competitive advantage for probiotics. For example, spontaneous sauerkraut fermentations operate optimally with a concentration of 2.5% ( w / w ) NaCl [ 85 ], while 2 to 3% salt in meat fermentation was demonstrated to improve meat texture [ 86 ]. All tested isolates were resistant to 1.5% NaCl, with L. plantarum being the most resistant to higher NaCl concentrations ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Texture received the lowest score, which can be attributed to the NaCl addition. Indeed, NaCl has been extensively reported to affect the texture of sauerkraut in a concentration-dependent way [46,47]. More accurately, Wolkers-Rooijackers et al [46] reported that sauerkraut produced with 15 g/kg of NaCl had better texture, in terms of firmness, compared to that produced with a lower NaCl content (9 g/kg).…”
Section: Discussionmentioning
confidence: 99%